Automated compounding technology and workflow solutions for the preparation of chemotherapy: a systematic review. Issue 6 (21st August 2019) - Batson, Sarah; Mitchell, Stephen A; Lau, Davina; Canobbio, Michela; de Goede, Anna; Singh, Inderjit; Loesch, Ulrich
Abstract : Objectives: The current systematic review (SR) was undertaken to summarise the published literature reporting the clinical and economic value of automation for chemotherapy preparation management to include compounding workflow software and robotic compounding systems. Methods: Literature searches were conducted in MEDLINE, Embase and the Cochrane Library on 16 November 2017 to identify publications investigating chemotherapy compounding workflow software solutions used in a hospital pharmacy for the preparation of chemotherapy. Results: 5175 publications were screened by title and abstract and 18 of 72 full publications screened were included. Grey literature searching identified an additional seven publications. The SR identified 25 publications relating to commercial technologies for compounding (Robotic compounding systems: APOTECAchemo (n=12), CytoCare (n=5) and RIVA (n=1); Workflow software: Cato (n=6) and Diana (n=1)). The studies demonstrate that compounding technologies improved accuracy in dose preparations and reduced dose errors compared with manual compounding. Comparable levels of contamination were reported for technologies compared with manual compounding. The compounding technologies were associated with reductions in annual costs compared with manual compounding, but the impact on compounding times was not consistent and was dependent on the type of compounding technology. Conclusions: The published evidence suggests that the implementation of chemotherapy compounding automation solutions may reduce compounding errors and reduce costs; however, this is highly variable depending on the form of automation. In addition, the available evidence is heterogeneous, sparse and inconsistently reported. A key finding from the current SR is a 'call to action' to encourage pharmacists to publish data following implementation of chemotherapy compounding technologies in their hospital, which would allow for evidence-based recommendations on the benefits of chemotherapy compounding technologies.